Immunological effects of competitive versus recreational sports in cross-country skiing - Müller, O.; Villiger, B.; O'Callaghan, B.; Simon, H. U. (International Journal of Sports Medicine, 2001)
For a period of two months during the competitive season the effects of endurance training in cross-country skiers were evaluated in order to compare the adaptive and innate immune systems between 10 competitive athletes, 10 moderately trained athletes and 10 untrained healthy controls. The main results were as follows: the peripheral T-lymphocyte count of the competitive athletes was decreased. In contrast the number of peripheral blood NK cells was increased in this group. These data imply a diminution of the adaptive immune system due to repeated bouts of intense exercise and contemporaneous reinforcement of the innate immune response. Moreover the inducible IL-12-expression following monocyte stimulation was significantly decreased in competitive athletes. Compared with the other two groups, the moderately trained athletes showed a significantly increased production of IFN-? upon T-cell stimulation. These data suggest that the immune system may profit from moderate endurance training by an increased capacity to generate IFN-? while the immune situation following repeated exhausting exercise of competitive athletes tends to deteriorate through downregulation of IFN-? and IL-12.